VOSVIEWER SOFTWARE AS A TOOL IN ANALYZING THE BIBLIOMETRIC OF WATCHKEEPING ONBOARD SHIPS - Sulistiyowati, Ely; Indriyani, Kristin Anita; Nurhidayati, Indah; Kundori, Kundori (UNIMAR AMNI Semarang, 2024)
This article aims to conduct bibliometric research on ship crew members who carry out guard duty on ships. Research gaps in watch keeping studies are identified and analyzed. Ship crews carrying out guard duty must ensure ship safety and avoid the risk of ship accidents. The method used in this research is descriptive qualitative, namely by describing data visualization. The keyword chosen is